Effect of In Vitro Ruminal pH on Zearalenone Degradation and Interaction with Other Mycotoxins in a Static Gastrointestinal Model - Rimvydas Falkauskas; Jurgita Jovaišienė; Gintarė Vaičiulienė; Sigita Kerzienė; Ingrida Jacevičienė; Eugenijus Jacevičius; Inga Jarmalaitė; Marija Ivaškienė; Gintaras Daunoras; Rasa Želvytė; Violeta Baliukonienė (Toxins)
The degradation of zearalenone (ZEN) in the rumen of dairy cows is influenced by rumen pH, which is a key factor affecting this process. The aim of this study was to investigate the variation of ZEN in interaction with other mycotoxins at different ruminal pH environments (physiological (pH 6.5) and acidic (pH 5.5)) using an in vitro rumen model. Rumen fluid was collected from the caudoventral part of the rumen of cows using a pharyngeal–esophageal probe. To determine the changes in different mycotoxins (ZEN; AFLB1; DON; T-2) in the rumen of cows, a model rumen system was used, and mycotoxins concentrations were detected by HPLC. The study found that at pH 6.5, ZEN alone and in combination with other mycotoxins (DON; T-2; AFLB1) significantly (p < 0.05) reduced ZEN levels compared to the rumen environment at pH 5.5. It was observed that α-zearalenol (α-ZEL) and β-zearalenol (β-ZEL) concentrations were generally higher at a rumen pH of 6.5 compared to pH 5.5, averaging 47.09 µg/L and 35.23 µg/L, respectively. Additionally, the frequency of detection for both α-ZEL and β-ZEL was greater at pH 6.5 than at pH 5.5. A comparison of α-ZEL concentrations in rumen samples at pH 5.5 showed a 20% increase from the 6th to the 9th hour of the test, while β-ZEL levels remained unchanged over the same period.